Ghanaian Indigenous Conception of Real Mathematics Education in Teaching and Learning of Mathematics - Ali, Clement Ayarebilla (Indonesian journal of science and mathematics education, 2021)
Ghana abounds in indigenous resources but little mathematics has been conceptualised. The study therefore applied the four trends of real mathematics education on five main Ghanaian indigenous materials. The design was quasi-experimental non-equivalent groups of experimental (80) and control (70) students. The experimental group was taught with the four trends and the control with the traditional approach. The researcher used teacher-made test instruments through the standard psychometric techniques and tagged them as pretest and post-test scores. Both tests were similar and given to both groups before and after the treatments. The results show that the main indigenous Ghanaian materials were signs/symbols, artefacts, instruments, tools and technologies, and signs/symbols being the most significant. These results were then applied to the teaching and learning of mathematics at the senior high school levels. The researcher therefore recommends that students should be allowed to use indigenous mathematical ideas, concepts, generalizations and thoughts processes